Parental Smoking During Pregnancy and Its Association with Low Birth Weight, Small for Gestational Age, and Preterm Birth Offspring: A Birth Cohort Study - Ting-Jung Ko; Li-Yi Tsai; Li-Ching Chu; Shu-Jen Yeh; Cheung Leung; Chien-Yi Chen; Hung-Chieh Chou; Po-Nien Tsao; Pau-Chung Chen; Wu-Shiun Hsieh (Pediatrics and Neonatology)
Intrauterine exposure to tobacco smoke has been discerned as an important risk factor for low birth weight (LBW), small for gestational age (SGA), and preterm birth infants. In this cohort study, we investigated the association of the amount of parental smoking during the different pregnancy stages with birth weight and the incidence of preterm delivery. Methods: Our study population was acquired from the Taiwan Birth Cohort Study. Between June 2005 and July 2006, 21,248 postpartum women were interviewed 6 months after their deliveries by a structured questionnaire. The parents were divided into four groups according to the amount of smoking during preconception, the first trimester, and the second and third trimesters. The relationships of parental smoking with gestational age and birth weight during the different pregnancy stages were assessed using multivariate linear regression. Multiple logistic regression analyses were performed to estimate the odds ratios and 95% confidence intervals of preterm delivery, LBW, and SGA infants during the different parental smoking status and the different pregnancy stages. Results: After adjusting for the physical and socioeconomic status of the parents and for paternal smoking during the same period, we found that maternal smoking decreased birth weight. Compared with the nonsmoking groups, all the maternal smoking groups had higher incidences of LBW, SGA, and preterm birth infants, especially when the mothers smoked >20 cigarettes/day. The association of paternal smoking with LBW, SGA, and preterm birth infants was insignificant. Conclusion: Maternal smoking is responsible for increased incidences of LBW and preterm delivery of babies, and therefore, smoking cessation/reduction should be advised to pregnant women to reduce morbidities in their neonates. Further studies are needed to clarify the correlation of fetal health with passive smoking, including exposure to environmental tobacco smoke and to other smokers in the family.